THE ROLE OF BILINGUALISM IN THE FORMATION OF CULTURAL AND LINGUISTIC IDENTITY - Pulatova Gulnoza Murodilovna (Bright Mind Publishing, 2025)
This article describes the concept of bilingualism, the emergence of bilingualism and its socio-cultural conditions. The study of a second language, the transformation of the ethnic identity of a bilingual person in bilingvs, the emergence of the phenomenon of two cultures and the simultaneous transformation into a carrier of two cultures are given.
Keywords: Language, bilingualism, dialect, psycholinguistics, globalization, ethnography.